The Grotte du Placard at 150 : new considerations on an exceptional prehistoric site - Delage, Christophe, (Archaeopress Publishing Ltd, 2018)
The prehistoric site of Le Placard, Southwest France, was first explored 150 years. 19th-century excavations almost emptied the cavity, now surprisingly ill-known. This 150-year milestone grants an opportunity to look back at this exceptional site and what it can tell us about the Late Pleistocene hunting and gathering societies who dwelt there.